A case report of a symptomatic right anomalous coronary artery with concomitant atherosclerotic disease: the benefit of a sequential comprehensive non-invasive and invasive diagnostic approach. Issue 3 (4th March 2021) - Bigler, Marius Reto; Huber, Adrian Thomas; Räber, Lorenz; Gräni, Christoph
Abstract: Background : Anomalous aortic origin of a coronary artery (AAOCA) is a rare congenital disease associated with an increased risk of myocardial ischaemia, ventricular arrhythmias, and heart failure. Case summary : A 75-year-old Caucasian man was referred for invasive coronary angiography (ICA) due to atypical chest pain. Invasive coronary angiography demonstrated non-significant atherosclerotic disease of the left coronary artery and an anomalous origin of the right coronary artery (RCA); without selective intubation. Coronary computed tomography angiography (CCTA) revealed a right-AAOCA with interarterial and intramural course, and a soft plaque in the distal RCA. Subsequent physical-stress single-photon emissions computed tomography (SPECT) showed exercise-induced inferoapical myocardial ischaemia, giving a Class IC level of evidence for surgical correction of the AAOCA. Repeated ICA with selective R-AAOCA intubation confirmed an 80% distal atherosclerotic stenosis, which was treated with direct stenting. Subsequent invasive physiologic evaluation under maximal dobutamine-volume challenge (gradually increasing dose of dobutamine max. 40 μg/kg per body weight/min, 3000 mL ringer lactate and 1 mg atropine was given until the patient reached a maximum of 145 b.p.m.), revealed a haemodynamically non-relevant anomalous segment with a fractional flow reserve (FFR) of 0.91. A follow-up SPECT was normal, and the patient was completely symptom-free at 1 month. Discussion : We present the sequential diagnostic approach in a symptomatic patient with a right anomalous coronary artery and concomitant atherosclerotic disease. Using this approach, the patient could be deferred from guideline recommended open-heart surgery of the AAOCA, as direct invasive dobutamine/volume FFR revealed haemodynamic non-relevance of the anomalous segment after stenting the concomitant atherosclerotic stenosis in the distal segment within the same coronary artery.